2020
DOI: 10.1002/jcp.29534
|View full text |Cite
|
Sign up to set email alerts
|

Male fertility in Mus musculus requires the activity of TRYX5 in sperm migration into the oviduct

Abstract: Nowadays, abnormal loss of serine proteases appears very frequently in male patients with unexplained sterility. In fact, many testis-specific serine proteases, the largest family among the four protease families implicated in murine spermatogenesis, are indispensable for reproduction. In the present study, we demonstrate that the previously uncharacterized testis-specific serine protease TRYX5 (1700074P13Rik) is required for male fertility in mice. Tryx5 −/− male mice are sterile, yet they have normal spermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Recent research suggested that serine protease TRYX5 may participate in the post-translational modification (PTM) of ADAM3 through an indirect way in the Golgi, and loss of TRYX5 may bring precursor ADAM3 into an unstable state and disappear in elongated spermatid of S13-16 stages owing to the lack of PTM (Zhang et al, 2020). In addition to testis-specific factors, a ubiquitously expressed protein, TPST2 ( protein-tyrosine sulfotransferase 2), is also related to ADAM3 quality control occurring past the ER, precisely in the ER-Golgi intermediate compartment and in the Golgi (Marcello et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research suggested that serine protease TRYX5 may participate in the post-translational modification (PTM) of ADAM3 through an indirect way in the Golgi, and loss of TRYX5 may bring precursor ADAM3 into an unstable state and disappear in elongated spermatid of S13-16 stages owing to the lack of PTM (Zhang et al, 2020). In addition to testis-specific factors, a ubiquitously expressed protein, TPST2 ( protein-tyrosine sulfotransferase 2), is also related to ADAM3 quality control occurring past the ER, precisely in the ER-Golgi intermediate compartment and in the Golgi (Marcello et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that sperm from mice deficient for the serine protease PRSS37 or PRSS55 failed to migrate from the uterus into the oviduct and impaired sperm-egg binding, and was accompanied by the disappearance of mature ADAM3 on the sperm surface (Shang et al, 2018;Shen et al, 2013). Most recently, mice deficient for a trypsin-like serine protease, TRYX5, also displayed a similar phenotype as that of Prss37 −/− and Prss55 −/− mice (Zhang et al, 2020). However, it is still unclear how these serine proteases mediate ADAM3 maturation, contributing to male fertility.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A group of genes encoding proteases, enzymatically inactive pseudoproteases, and protease inhibitors is apparently associated with the same physiological function, i.e., maturation of sperm conferring abilities to migrate into female oviduct and bind with zona pellucida. Ablation of Tmprss12 ( 66 ), Prss55 ( 67 , 68 ), Tryx5 ( 69 ), Prss37 ( 70 ), Ace ( 71 ), Adam1a ( 72 ), Adam2 ( 73 ), Adam3 ( 74 , 75 ), and Adam6 ( 76 ) results in deficient sperm migration into the oviduct and binding to the zona pellucida of eggs. Among them, Adam1a , Adam2 , Adam3 , Adam6 , and Prss37 encode catalytically inactive pseudoproteases.…”
Section: Multicellular Organisms Ii: Vertebratesmentioning
confidence: 99%
“…PRSS37 supports ADAM3 precursor translocation to the sperm cell surface by collaborating with PDILT, a testis-specific protein disulfide isomerase indispensable for ADAM3 surface expression ( 197 , 198 ). TMPRSS12, PRSS55, and TRYX5, all of which are serine proteases and retain catalytic triad residues, are necessary for the production or stable localization of processed ADAM3 on the cell surface of epididymal spermatozoa ( 66 69 ), although it remains uncertain whether these proteases directly cleave ADAM3.…”
Section: Multicellular Organisms Ii: Vertebratesmentioning
confidence: 99%